1978
DOI: 10.1111/j.1365-2265.1978.tb01510.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Oestrone and Oestradiol Following Spironolactone Administration in Hypertensive Men

Abstract: The present study was undertaken to evaluate long-term effects of spironolactone on basal serum oestrone, oestradiol, testosterone, LH and prolactin concentrations in hypertensive male patients. Serum prolactin response to TRH was also evaluated. Patients were divided into two groups: a conventional-dosage group, consisting of six males with essential hypertension who took 75 to 150 mg of spironolactone daily for 12 weeks, and a high-dosage group, consisting of two males with idiopathic hyperaldosteronism who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The mean immunological potency of LER-907 was 255.0 mlU/jug in the LH assay. The intra-and interassay coefficients of variation of a pool of serum from normal men were 7.0% and 14.0%, respectively (24). The serum PRL concentration was measured by a previously described homologous double antibody RIA (25).…”
Section: Hormone Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean immunological potency of LER-907 was 255.0 mlU/jug in the LH assay. The intra-and interassay coefficients of variation of a pool of serum from normal men were 7.0% and 14.0%, respectively (24). The serum PRL concentration was measured by a previously described homologous double antibody RIA (25).…”
Section: Hormone Measurementsmentioning
confidence: 99%
“…Serum testosterone was measured by a previously published RIA method (24). The intra-and interassay coefficients of variation of a pool of serum from normal men were 5.64% and 11.2%, respectively.…”
Section: Hormone Measurementsmentioning
confidence: 99%
“…Weak inhibition of androgen synthesis and increased conversion of androgens to estrogens were irregularly demonstrated and are probably minor. 10,11 Animal studies have shown an increased rate of neoplasia, including breast carcinoma, in rats on high-dose canrenoate, another aldosterone antagonist which shares a common metabolite (canrenone) with spironolactone. 12 Some cases of breast carcinoma in women under spironolactone therapy have been reported, but this association may only be fortuitous.…”
Section: Discussionmentioning
confidence: 99%
“…Although several explanations have been provided, the most likely mechanism of these side effects is the lack of specificity of spironolactone as it binds, as already mentioned, not only to the renal aldosterone receptor, but also to the progesterone receptor and the dihydrotestosterone receptor (MIYAKE et al 1978;CORVOL et al 1975;BONNE and RAYNAUD 1974).…”
Section: Sexual Functions and Endocrine Disordersmentioning
confidence: 99%